2017
DOI: 10.1186/s12864-017-3612-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing of HPV E6/E7 genes reveals loss of genotypic diversity and gain of clonal dominance in high-grade intraepithelial lesions of the cervix

Abstract: BackgroundHuman papillomavirus (HPV) is the carcinogen of almost all invasive cervical cancer and a major cause of oral and other anogenital malignancies. HPV genotyping by dideoxy (Sanger) sequencing is currently the reference method of choice for clinical diagnostics. However, for samples with multiple HPV infections, genotype identification is singular and occasionally imprecise or indeterminable due to overlapping chromatograms. Our aim was to explore and compare HPV metagenomes in abnormal cervical cytolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 44 publications
3
32
0
Order By: Relevance
“…Although Sanger sequencing is still the gold standard, it lacks the resolution generated by next-generation sequencing (NGS) techniques. Only the major variant driving the infection can be reliably determined, and any coinfections present in the samples cannot be reliably identified ( 15 ). On the other hand, major variants have been implicated in causing persistent infections, while minor variants appear more transient in nature ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Sanger sequencing is still the gold standard, it lacks the resolution generated by next-generation sequencing (NGS) techniques. Only the major variant driving the infection can be reliably determined, and any coinfections present in the samples cannot be reliably identified ( 15 ). On the other hand, major variants have been implicated in causing persistent infections, while minor variants appear more transient in nature ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting result is that men with multiple HPV types had a significant higher risk of an abnormal cytological finding as compared to men with single HPV infection even in the absence of with HPV 16. A recent study by Shen-Gunter et al [ 17 ] analyzed the HPV genotypes and their proportional composition in single- and multi-infected cervical samples to explore viral diversity and characterize differences in metagenomes. They identified in LSIL/HSIL samples many HPV genotypes and the dominant(most abundant) genotypes mainly included the HPV-16 genotype; the other observed genotypes were the HPV-35 and -39.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the diagnosis of AIDS, previous data showed that it is a risk factor for SIL [ 4 , 17 ]; Goedert and colleagues [ 19 ], reported that the relative risk of HSIL development is 31.7 after the diagnosis of AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…In fact recent studies performing deep sequencing of HPV E6/E7 genes have revealed loss of genotypic diversity and clonal dominance in high-grade intraepithelial lesions of the cervix. The differences in carcinogenic potential among various HPV genotypes are related tothe evolutionary distances between HPV species (measured using HPV L1 or E6/7 genes) which correlate with the level of IARC-defined carcinogenicity [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%